In vitro validation study of HER2 and HER4 mutations identified in an ad hoc secondary analysis of the LUX-Lung 8 randomized clinical trial. (December 2021) - Hamada, Akira; Suda, Kenichi; Koga, Takamasa; Fujino, Toshio; Nishino, Masaya; Ohara, Shuta; Chiba, Masato; Shimoji, Masaki; Takemoto, Toshiki; Soh, Junichi; Uchida, Tetsuro; Mitsudomi, Tetsuya
Highlights: Several HER2/4 VUS were identified in lung SCC patients in the LUX-Lung 8 trial. We examined the transforming ability of these HER2/4 VUS and sensitivity to TKIs. HER2 mutations E395K, G815R, and R929W showed transforming ability in Ba/F3 models. 2G/3G TKIs, but not erlotinib, were active for Ba/F3 cells with these mutations. These results suggest that HER2 mutations may be therapeutic targets in lung SCC. Abstract: Objectives: The LUX-Lung 8 randomized trial (LL8) demonstrated a prolonged progression-free survival (PFS) in patients with metastatic squamous cell carcinoma (SCC) of the lung after treatment with afatinib compared with erlotinib. A secondary analysis of the LL8 reported that the presence of rare HER2/HER4 mutations may be partly responsible for this result. Patients with HER2 (hazard ratio [HR] 0.06/ p-value 0.02 ) or HER4 (HR 0.21/ p-value unreported ) mutations had longer PFS after treatment with afatinib. However, the biological function of these mutations is unclear. Materials and Methods: Ten HER2 and 13 HER4 point mutations that were detected in the secondary analysis were transduced into the mouse pro-B cell line (Ba/F3) to determine changes in interleukin-3 (IL-3) dependence and sensitivity to six EGFR or pan-HER tyrosine kinase inhibitors (TKIs), including afatinib and erlotinib. The efficacy of the six TKIs was compared using a sensitivity index, defined as the 50% inhibitory concentration divided by trough concentration of each drug at clinically recommended doses. Results: Seven out of 10 Ba/F3 clones expressing HER2 mutations and all 13 Ba/F3 clones expressing HER4 mutations did not grow in the absence of IL-3, indicating these mutations were non-oncogenic. Three Ba/F3 clones expressing the HER2 mutations E395K, G815R, or R929W acquired IL-3-independent growth. The sensitivity indices for afatinib were ≤ one-fifth of those for erlotinib in all three lines. Other second/third-generation (2G/3G) TKIs showed high efficacy against clones expressing these HER2 mutations. Conclusions: The majority of HER2/4 mutations detected in lung SCC from LL8 were not oncogenic in the Ba/F3 models, suggesting that the presence of HER2/4 mutations were not responsible for the superior outcomes of afatinib in the LL8 study. However, SCC of the lung in some patients may be driven by rare HER2 mutations, and these patients may benefit from 2G/3G pan-HER-TKI treatment.